2022
DOI: 10.3390/ijms23095121
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Pleiotropic Signatures of Regulatory SNPs in Zea mays L. Using Multi-Omics Data and Machine Learning Algorithms

Abstract: Maize is one of the most widely grown cereals in the world. However, to address the challenges in maize breeding arising from climatic anomalies, there is a need for developing novel strategies to harness the power of multi-omics technologies. In this regard, pleiotropy is an important genetic phenomenon that can be utilized to simultaneously enhance multiple agronomic phenotypes in maize. In addition to pleiotropy, another aspect is the consideration of the regulatory SNPs (rSNPs) that are likely to have caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…Feature selection was used in recent studies to increase the prediction accuracy of genomic prediction models in man 59 and crops. 51,54 However, these studies led to heterogeneous results such that no general recommendation can be given regarding feature selection. Here, we show that in case of rhizomania resistance, prediction accuracy could be increased using feature selection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Feature selection was used in recent studies to increase the prediction accuracy of genomic prediction models in man 59 and crops. 51,54 However, these studies led to heterogeneous results such that no general recommendation can be given regarding feature selection. Here, we show that in case of rhizomania resistance, prediction accuracy could be increased using feature selection.…”
Section: Discussionmentioning
confidence: 99%
“…Besides improving prediction accuracy of genomic prediction models, other studies used results from feature selection via genomic prediction to determine the association between certain SNPs and the phenotype. 54,64 Following this approach, it could be interesting to use the method presented here to select the 29 single SNPs or the 16 SNP pairs, respectively, as being associated with rhizomania resistance. However, we found that the estimation of variable importance did not lead to the same results in each training data set.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another important application is the prediction of the effects of genetic variation 70 . While current genomics approaches rarely enable functional annotation of the effect of polymorphisms 71,72 and rely mostly on statistical association, an increasing availability of long-read data enables making mechanistic links between observed variation and the down-stream molecular network 32 . The presented example of gene expression across 14 tomato accessions represents an important step in this direction and opens perspectives for routine prediction pipelines for new genomes, tissues and environmental scenarios.…”
Section: Discussionmentioning
confidence: 99%